Agricultural statistics in india : a guide - Bansil, P. C. (New Delhi, 1984)
This work, which is being released in its third edition, has grown along with India's agriculture and is intend ed to be a source of reliable information on the subject.
Keywords: Agriculture Statistics; IES as an author; Indian Economics Service